Determinants of age-specific undernutrition in children aged less than 2 years—the Bangladesh context - Choudhury, Nuzhat; Raihan, Mohammad Jyoti; Sultana, Sabiha; Mahmud, Zeba; Farzana, Fahmida Dil; Haque, Md Ahshanul; Rahman, Ahmed Shafiqur; Waid, Jillian L.; Chowdhury, Atique Mushtaque Raza; Black, Robert E.E.; Ahmed, Tahmeed J. (© 2017 Blackwell Publishing Ltd., 2018)
This article was published in the Maternal and Child Nutrition [© 2016 John Wiley & Sons Ltd] and the definitive version is available at: https://doi.org/10.1111/mcn.12362 The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/mcn.12362/abstract;jsessionid=3D72B283C6E6372703E478D5258C9C7E.f02t04